Impacts of human activities on the supply of marine ecosystem services: A conceptual model for offshore wind farms to aid quantitative assessments. Issue 3 (March 2023) - Van de Pol, Lennert; Van der Biest, Katrien; Taelman, Sue Ellen; De Luca Peña, Laura; Everaert, Gert; Hernandez, Simon; Culhane, Fiona; Borja, Angel; Heymans, Johanna J.; Van Hoey, Gert; Vanaverbeke, Jan; Meire, Patrick
Abstract: Increased pressures from human activities may cause cumulative ecological effects on marine ecosystems. Increasingly, the study of ecosystem services is applied in the marine environment to assess the full effects of human activities on the ecosystem and on the benefits it provides. However, in the marine environment, such integrated studies have yet to move from qualitative and score-based to fully quantitative assessments. To bridge this gap, this study proposed a 4-tiered method for summarizing available knowledge and modelling tools to aid in quantitative assessments of ecosystem services supply. First, the ecosystem functioning mechanisms underlying the supply of services are conceptually mapped. Second, the impacts of the human activity of interest are summarized and linked to the first conceptual model in a case-specific model of ecosystem services supply. Third, indicators are selected that would best represent changes in the most important parameters of the conceptual model in a quantitative manner. Fourth, the knowledge gained in the previous steps is used to select models that are most useful to quantify changes in ecosystem services supply under the human pressure of interest. This approach was applied to the case study of offshore wind energy in the Belgian part of the North Sea, which is one of the most rapidly expanding industries in the marine environment globally. This study provides a useful tool to proceed towards quantification of marine ecosystem services, highlighting the need for a fully integrated approach to developing environmental impact assessment tools. Graphical abstract: Image 1